Hate crimes: American and Balkan experience - Ćirić Jovan (Temida)
In the nineties of the last century it was noticed in the U.S.A. that suddenly the number of crimes with violence in the inter-racial and inter-ethnical conflicts rose. Also the phenomenon of ignition of churches, religious and sacral objects, especially in the south of the U.S.A., objects which were used by black people, was recorded. Directly in relation to that - the term „hate crimes“ then arose in science and became outspread very quickly, primarily in criminology. Several events, and above all the murder of a young homosexual in Wyoming influenced for both the violence and the crimes commited towards the homosexuals and all due to the prejudices towards this sexual minority to be included in this term. Today, this term is used not only in the U.S.A. and not only in a criminological sense, but also in a purely legal sense to denote the crimes which were carried out under the influence of hate towards a correspondent racial, ethnical or sexual minority. This term is linked also to the terminology and thus the problems which are related to the „hate speech“. The author of this paper writes about how this term arose in the first place and which problems emerge related to hate crimes and primarily in relation to the issues of expansion of democracy and tolerance, and also education, primarily among the police force and the young population. The author also ascertains that only with the law, no great effects in the battle against this phenomenon can be achieved and that before the criminal-legal intervention some other measures have to be approached, like the creation of an atmosphere of tolerance and the education of the citizens about the phenomenon of hate crimes.